Ready for the change: strengthening adaptive responses to a looming career transition - Horst, Anna Cornelia van der; Justus Liebig University Giessen (My University, 2018)
Today s world of work requires workers to adapt their careers to ever-changing demands and circumstances. To adapt successfully, they have to be well prepared, see the need, and know the tools for managing their own careers - a possible challenge at all career stages. According to career construction theory, adaptivity, career adaptability and adaptive responses are crucial to prepare for and successfully deal with career transitions. This dissertation provides new insights and tools for scholars and practitioners who aim to help workers manage their own careers, prepare for transitions, and adapt successfully. A correlational study addressing the relationships between age, adaptivity and adaptive responses shows how some people naturally possess the demographic factors or psychological characteristics that make it easier for them to adapt, while others struggle to show the necessary responses. Therefore, effective interventions that can help workers find their own path in the world of work are necessary and should be available to as many people as possible. The two intervention studies in this dissertation focus on students and on experienced workers and validate an intervention that combines an online portfolio with a group event. The outcomes show that it is possible to offer students and workers an efficient, scalable and effective intervention to enhance their abilities to adapt and deal with the changes and transitions they face in their working life.
Keywords: ddc:150